The Impact of Technology on the Diagnosis of Congenital Malformations. Issue 11 (26th June 2019) - Straub, Loreen; Huybrechts, Krista F; Bateman, Brian T; Mogun, Helen; Gray, Kathryn J; Holmes, Lewis B; Hernandez-Diaz, Sonia
Abstract: As technology improves and becomes more widely accessible, more subclinical congenital malformations are being detected. Using a cohort of 1, 780, 156 pregnant women and their offspring nested in the 2000–2013 US Medicaid Analytic eXtract, we contrasted time trends in malformations which do not necessarily present with overt clinical symptoms early in life and are more likely to be diagnosed via imaging (secundum atrial septal defect, patent ductus arteriosus, ventricular septal defect, pulmonary artery anomalies, pulmonary valve stenosis, hydrocephalus) with trends in malformations that are unlikely to escape clinical diagnosis (tetralogy of Fallot, coarctation of the aorta, transposition of the great vessels, hypoplastic left heart syndrome, oral cleft, abdominal wall defect). Logistic regression was used to account for trends in risk factors while assessing the impact of increased screening intensity. Prevalence of the diagnosis of secundum atrial septal defect rose from 2.3‰ in 2000–2001 to 7.5‰ in 2012–2013, of patent ductus arteriosus from 1.9‰ to 4.1‰, and of ventricular septal defect from 3.6‰ to 4.5‰. Trends were not explained by changes in the prevalence of risk factors but were attenuated when accounting for screening tests. The other malformations showed no temporal trends. Findings suggest that increased screening partially explains the observed increase in diagnosis of milder cases of select common malformations.